2018
DOI: 10.1080/14767058.2018.1491031
|View full text |Cite
|
Sign up to set email alerts
|

The fetal fibronectin test: 25 years after its development, what is the evidence regarding its clinical utility? A systematic review and meta-analysis

Abstract: The fetal fibronectin test should not be used as a screening test for asymptomatic women. For high-risk asymptomatic women, and especially for women with multiple pregnancies, the performance of the fetal fibronectin test was also too low to be clinically relevant. Consensual use as a diagnostic tool for women with suspected preterm labor, the best use policy probably still depends on local contingencies, future cost-effectiveness analysis, and comparison with other more recent available biochemical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 403 publications
0
13
0
Order By: Relevance
“…For high-risk asymptomatic pregnant women, and especially for women with multiple pregnancies, the predictive value of the test was also too low for clinical practice. 17 Another review and meta-analysis did suggest that although management based on fFN results may reduce PTB, the evidence was found to be of low quality. 18 A prospective observational cohort study with 9410 nulliparous women of singleton pregnancies shows that quantitative vaginal fFN and serial transvaginal ultrasound cervical length had limited predictive value for PTB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For high-risk asymptomatic pregnant women, and especially for women with multiple pregnancies, the predictive value of the test was also too low for clinical practice. 17 Another review and meta-analysis did suggest that although management based on fFN results may reduce PTB, the evidence was found to be of low quality. 18 A prospective observational cohort study with 9410 nulliparous women of singleton pregnancies shows that quantitative vaginal fFN and serial transvaginal ultrasound cervical length had limited predictive value for PTB.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis found that fFN should not be used as a screening test for asymptomatic pregnant women. For high‐risk asymptomatic pregnant women, and especially for women with multiple pregnancies, the predictive value of the test was also too low for clinical practice 17 . Another review and meta‐analysis did suggest that although management based on fFN results may reduce PTB, the evidence was found to be of low quality 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[300] MMPs -1, -2, -8, -9, -12 [125] Elastin-derived matrikine, VG-6 (VGVAPG), AG-9 (AGVPGLGVG) [125,241,301,302] Elastin receptor complex (ERC) [300] Fibrillin [298] ADAMTS -10, -6 [303] Integrins αVβ3, αVβ6, α5β1 [304,305] Fibronectins [29,[306][307][308][309] Yes MMPs -2, -3, -7, -10, -11 [297] Fibronectin fragments (FNFr) [310], anastellin [311], fibstatin [312] Integrins α5β1 [313], α9β1, α4β1, αv-integrins [309,314,315], growth factors and syndecans [316] Fibronectin ED-A [29] Integrins α9β1, α4β1, α5β1, αv-integrins [29,308,317] Marks tumor stroma [29,[306][307][308]315,[317][318][319][320] Fibronectin ED-B [29] Integrins α9β1, α4β1, α5β1, αv-integrins [29,308,317] Marks tumor stroma [29,[306][307][308]…”
Section: Elastic Fibrilsmentioning
confidence: 99%
“…The other method to improve the accuracy of threatened SPTL diagnosis in symptomatic women was measurement of fetal fibronectin (fFN). Systematic reviews and meta-analyses [8,9] found that fFN should not be used as a screening test, and its predictive value was also too low for clinical practice for high-risk pregnancies. These studies do not support routine application of these tests in the clinic of pregnancies at risk of SPTL [7][8][9].…”
Section: The Efficacy and Efficiency Of Uterocervical Angle Measuremementioning
confidence: 99%